Bibliometric Analysis of Excessive Electricity Consumption in the Context of Economic and Ecological Awareness - Janus, Dorota; Kyć, Grzegorz; Zema, Tomasz (Analiza bibliometryczna nadmiernego zużycia energii elektrycznej w kontekście świadomości ekonomicznej i ekologicznej, 2023)
Excessive electricity consumption in households is a common phenomenon in taking part of household budgets. In a situation where many countries are facing increase in electricity prices, limiting electricity consumption is an important objective from both the economic and environmental perspectives. The analysis included consumer habits, behaviour and factors related to the exploitation of electrical equipment which may lead to unwanted electrical energy waste in households. Suggestions for examples of solutions to reduce excessive energy consumption were presented in an empirical perspective, based on the bibliometric analysis followed by the literature review. The aim of this study was to examine and map out household electricity consumption patterns, trends and the significant factors contributing to energy wastage. The results of scientific research on the economic and environmental awareness of consumers in the field of excessive energy consumption were also compiled. This paper may become an inspiration for further and more detailed quantitative and qualitative research on electrical energy waste – not only in households but also in public institutions or organisations.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 32-39
Keywords: economy; electrical energy; environment; household; electricity waste; gospodarka; energia elektryczna; środowisko; gospodarstwo domowe; odpady